2018
DOI: 10.1212/wnl.0000000000005684
|View full text |Cite
|
Sign up to set email alerts
|

Baseline NAWM structural integrity and CBF predict periventricular WMH expansion over time

Abstract: CBF and DTI measures independently predict WMH growth over time. DTI is a more sensitive predictor of WMH growth than CBF, with WMH progression likely due to demyelinating injury secondary to low perfusion. Findings support the use of MD as a sensitive marker of NAWM vulnerability in future trials aimed at preserving WM integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 33 publications
8
94
0
Order By: Relevance
“…These findings are also consistent with previous results that observed a “penumbra” in white matter areas within close proximity to WMH that was most vulnerable to later development of WMH [2022]. Interestingly, those studies suggest that WMH represent a “tip of the iceberg” phenomenon in which white matter microstructure and cerebral blood flow abnormalities extend beyond the identified borders of WMH (2-9mm and 13-14mm, respectively)[14] and portend the later development of frank WMH. Our findings complement these observations by demonstrating that there is lower white matter microstructure potentially decades prior to the development of WMH, and suggest that regional differences in white matter maturation lead to differential susceptibility to chronic hypoperfusion and contribute to the development of WMH.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These findings are also consistent with previous results that observed a “penumbra” in white matter areas within close proximity to WMH that was most vulnerable to later development of WMH [2022]. Interestingly, those studies suggest that WMH represent a “tip of the iceberg” phenomenon in which white matter microstructure and cerebral blood flow abnormalities extend beyond the identified borders of WMH (2-9mm and 13-14mm, respectively)[14] and portend the later development of frank WMH. Our findings complement these observations by demonstrating that there is lower white matter microstructure potentially decades prior to the development of WMH, and suggest that regional differences in white matter maturation lead to differential susceptibility to chronic hypoperfusion and contribute to the development of WMH.…”
Section: Discussionsupporting
confidence: 92%
“…The relationship between the distribution of the underlying FA measures and the occurrence of WMH has been shown in a longitudinal study of older adults [14], but our work shows that the relationship can be observed in adults as young as 20-30 years. The normative FA template was created from representative young, healthy adults.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations